Organic Fertilizer Efficiency for Food Security Support in Secanggang, Langkat - Hakim, Mukti; Wahyuni, Henny; Putri, Nazwa Dwi; Noviana, Monica (ITScience (Information Technology and Science), 2025)
The heavy reliance of Indonesian rice farmers on inorganic fertilizers has led to land degradation and declining productivity, necessitating a shift toward more sustainable approaches. This study analyses the technical efficiency of organic fertilizer use in rice farming in Secanggang Subdistrict, Langkat Regency, employing an input-oriented Data Envelopment Analysis (DEA) model on a sample of 45 farmers. Input variables include land area (0.2–1.2 ha), organic fertilizer quantity (200–500 kg/ha), labor (15–30 person-days/season), and production costs (IDR 3–5 million/season), while outputs consist of productivity (4–6 tons/ha) and income (IDR 8–12 million/season). The DEA results indicate an average technical efficiency of 78% under the Constant Returns to Scale (CRS) model and 85% under the Variable Returns to Scale (VRS) model, with 22% of farmers achieving optimal efficiency levels (>90%). Further analysis reveals that farmers cultivating more than 0.5 hectares attained 12% higher efficiency compared to those with smaller plots (p < 0.05), and farming experience of over 10 years contributed to an 8% efficiency increase (p < 0.1). Economically, organic fertilizer use reduced production costs by 15–20% through the substitution of chemical inputs and increased average seasonal income by approximately IDR 1.2 million. The key findings of this study are: (1) there is a 22% potential gain in efficiency through input optimization; (2) managerial factors (experience, education) have a greater influence on efficiency than technical factors; and (3) an organic fertilizer dosage of 300–400 kg/ha yielded the most efficient outcomes.